Oligodendrocyte morphometry and expression of myelin – Related mRNA in ventral prefrontal white matter in major depressive disorder. (June 2015) - Rajkowska, Grazyna; Mahajan, Gouri; Maciag, Dorota; Sathyanesan, Monica; Iyo, Abiye H.; Moulana, Mohadetheh; Kyle, Patrick B.; Woolverton, William L.; Miguel-Hidalgo, Jose Javier; Stockmeier, Craig A.; Newton, Samuel S.
Abstract: White matter disturbance in the ventral prefrontal cortex (vPFC) in major depressive disorder (MDD) has been noted with diffusion tensor imaging (DTI). However, the cellular and molecular pathology of prefrontal white matter in MDD and potential influence of antidepressant medications is not fully understood. Oligodendrocyte morphometry and myelin-related mRNA and protein expression was examined in the white matter of the vPFC in MDD. Sections of deep and gyral white matter from the vPFC were collected from 20 subjects with MDD and 16 control subjects. Density and size of CNPase-immunoreactive (-IR) oligodendrocytes were estimated using 3-dimensional cell counting. While neither density nor soma size of oligodendrocytes was significantly affected in deep white matter, soma size was significantly decreased in the gyral white matter in MDD. In rhesus monkeys treated chronically with fluoxetine there was no significant effect on oligodendrocyte morphometry. Using quantitative RT-PCR to measure oligodendrocyte-related mRNA for CNPase, PLP1, MBP, MOG, MOBP, Olig1 and Olig2, in MDD there was a significantly reduced expression of PLP1 mRNA (which positively correlated with smaller sizes) and increased expression of mRNA for CNPase, OLIG1 and MOG. The expression of CNPase protein was significantly decreased in MDD. Altered expression of four myelin genes and CNPase protein suggests a mechanism for the degeneration of cortical axons and dysfunctional maturation of oligodendrocytes in MDD. The change in oligodendrocyte morphology in gyral white matter may parallel altered axonal integrity as revealed by DTI. Highlights: Size and density of oligodendrocytes was examined in prefrontal white matter in depression. Sizes were smaller in subjects with depression as compared to controls. Expression of mRNA for myelin and oligodendrocyte markers was altered in depression. These changes may be related to white matter pathology reported by neuroimaging.